2022
DOI: 10.21873/invivo.12997
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Combined With Rapamycin Arrests Tumor Growth in a Patient-derived Orthotopic Xenograft (PDOX) Mouse Model of Dedifferentiated Liposarcoma

Abstract: Background/Aim: Dedifferentiated liposarcoma (DDLS) is a type of soft-tissue sarcoma with a poor prognosis due to distant metastasis and resistance to chemotherapy. The antimalarial drug chloroquine (CQ) can induce apoptosis in cancer cells. CQ in combination with rapamycin (RAPA), an mTOR inhibitor, has shown efficacy on osteosarcoma and other types of cancer. In the present study the efficacy of RAPA combined with CQ on the treatment of a DDLS patient-derived orthotopic xenograft (PDOX) model was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…As summarized in Table 1 (Ref. [35,50,52,53,55,57,58,60,61,63,66,67,[69][70][71]73,[75][76][77][78][79][80][83][84][85][86][87]), the roles of autophagy induced by rapamycin, temsirolimus as well as everolimus have not been shown to be consistent in preclinical studies. The primary role of the autophagic flux induced in response to everolimus is cytoprotective with a clinical trial performed by Haas et al [63] supporting the clinical utility of the autophagy inhibitor, HCQ, to improve everolimus clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized in Table 1 (Ref. [35,50,52,53,55,57,58,60,61,63,66,67,[69][70][71]73,[75][76][77][78][79][80][83][84][85][86][87]), the roles of autophagy induced by rapamycin, temsirolimus as well as everolimus have not been shown to be consistent in preclinical studies. The primary role of the autophagic flux induced in response to everolimus is cytoprotective with a clinical trial performed by Haas et al [63] supporting the clinical utility of the autophagy inhibitor, HCQ, to improve everolimus clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The same research group [85] also tested rapamycin in combination with CQ in vivo using patient-derived orthotopic xenograft mice models of dedifferentiated liposarcoma. The combination showed a marked tumor growth arrest as compared to each drug alone, together with increased apoptosis induced as showed by the TUNEL assay, more firmly arguing for a cytoprotective role for the autophagic process.…”
Section: Rapamycin and Autophagymentioning
confidence: 99%
“…We previously established a patient-derived orthotopic xenograft (PDOX) mouse model of dedifferentiated liposarcoma and showed that the combination of CQ and RAPA was effective in inhibiting tumor growth by inducing apoptosis (5). Excessive accumulation of autophagosomes has been shown to induce apoptosis in cancer cells (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…Well-differentiated liposarcomas (WDLS) can become dedifferentiated after repeated recurrence (3,4). We previously observed that the combination of the mTORinhibitor rapamycin (RAPA) and the anti-malarial drug chloroquine (CQ) had synergistic efficacy in a patient-derived orthotopic xenograft (PDOX) mouse model of dedifferentiated liposarcoma, with a high number of apoptosis-positive cancer cells (5).…”
mentioning
confidence: 99%
“…In MG63 osteosarcoma cells, CQ enhances apoptotic cell death promoted by mTOR inhibitor rapamycin (RAPA) by blocking the activity of downstream molecules of Akt/mTOR pathway 4E-BP1 and p70S6k, increasing the expression of autophagy-related proteins LC3-II and Atg12-Atg5, and decreasing the p62 level [78]. Although CQ was not effective as a single treatment, CQ/RAPA exposure induced apoptosis via the overaccumulation of autophagosomes in well-differentiated human liposarcoma (WDLS) 93T449 cells [79] and arrested the growth of dedifferentiated liposarcoma in mice bearing patient-derived orthotopic xenografts (DDLS PDOX) [103].…”
Section: Chloroquine and Pi3k/akt/mtor Inhibitorsmentioning
confidence: 99%